Made in India: Cisco reroutes innovation - REDDY, Srinivas K. (Institutional Knowledge at Singapore Management University, 2013)
This case describes the strategy adopted by Cisco India to develop the Advanced Services Router 901 (‘ASR 901’) which is a next generation 3G/LTE capable mobile backhaul and carrier Ethernet platform that is deployed at a cellular tower site or business premise to backhaul voice and data traffic into the core of the network. This was part of a larger strategy by Cisco headquarters to understand what could be built in the developing markets for the developing markets, as opposed to products conceived with only developed markets as the focus. Within a time frame of a few months, a team formed from scratch developed the ASR 901 completely – from conception to launch – at the Bangalore site in India. The ASR 901 successfully took on the challenge of delivering all the functionalities and features required by sophisticated telecoms clients, while meeting the specific requirements of its customers from the developing markets. It went on to win several awards, and interestingly, orders began streaming in from not just the developing economies (as had been expected) – but also from the tier-1 customers in the developed markets. ASR 901 was undoubtedly a milestone in Cisco India’s indigenous innovation initiatives. Could the lessons learnt while progressing through the several stages of developing this product be applied to similar new initiatives? Were the factors that contributed to the success of the ASR 901 generic enough to be applied as a template for innovation and product development from India?